Correlations between female breast density and biochemical markers - Kim, Ji-Hye (J Phys Ther Sci, 2015)
[Purpose] The aim of this study was to identify biochemical markers related to breast density. The study was performed with 200 patients who received mammography and biochemical marker testing between March 1, 2014 to October 1, 2014. [Subjects and Methods] Following the American College of Radiology, Breast Imaging Reporting and Data System (ACR BI-RADS), breast parenchymal pattern density from mammography was categorized into four grades: grade 1, almost entirely fat; grade 2, fibroglandular densities; grade 3, heterogeneously dense; and grade 4, extremely dense. Regarding biochemical markers, subjects underwent blood and urine tests after a 12-h fast. We analyzed correlations among breast density, general characteristics, and biochemical markers. [Results] Breast density-related factors were age, height, weight, body mass index (BMI), hematocrit, MCH, RDW, AST, ALT, ALP, uric acid, γGT, triglycerides, total cholesterol, HDL-cholesterol, and LDL-cholesterol. [Conclusion] The results can be used as basic and comparative data for the prevention and early control of breast cancer.